Youth awareness on financial fraud in Malaysia. - Yong, Edmund Jung Lin (2023)
The resource-based theory is used in this study to find the main factors (financial literacy, perception of internal control, security concern, ethical leadership, and fraud prevention initiatives) that can affect the youth financial fraud awareness level. The MOA theory was used in this study because it has been used in other studies to look at financial fraud awareness level.